PENGEMBANGAN VIDEO ICE BREAKING SEBAGAI MEDIA BIMBINGAN KONSELING DALAM MENINGKATKAN KETERAMPILAN SOSIAL - Muhammad Ilham Bakhtiar (Program Studi bimbingan Konseling PPs UNM Makassar, 2015)
This study is a research and development that examine the development of Ice Breaking as BK media to improve the social skills of students. The research objective is (1) To develop ice breaking video media as media that is acceptable BK (accepted), to improve the social skills of students. (2) To determine the effectiveness of video media as media BK ice breaking in improving students' social skills. Results of the research is a guide Ice Breaking and Video. The results showed that the development of the ice breaking video guide acceptabe (received), based on usefulness (utility), accuracy (accuracy), feasibility (faesibility) and relevance in improving the social skills of the students got decent results for use in SMA Negeri 1 Bontonompo. (2) Free video Ice breaking is very effective in improving the social skills of students in SMA Negeri 1 Bontonompo Gowa.